2013
DOI: 10.1007/s00280-013-2163-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of androgen deprivation therapy (ADT) plus chemotherapy as initial treatment for local failures or advanced prostate cancer

Abstract: The treatment demonstrated clinical benefit in all patient subsets with minimal reversible treatment-related adverse events. Subgroup analysis suggests that having prior local therapy resulted in greater PFS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…The standard therapy for advanced/metastatic disease has been androgen deprivation therapy (ADT). However, this approach often results in resistance and has recently become a less common therapeutic option [5]. Bilateral orchiectomy is one classical strategy for androgen suppression; however, this method is associated with numerous side effects and risk factors [4] and results in castration-resistant prostate cancer (CRPC).…”
Section: Current Treatments For Prostate Cancermentioning
confidence: 99%
“…The standard therapy for advanced/metastatic disease has been androgen deprivation therapy (ADT). However, this approach often results in resistance and has recently become a less common therapeutic option [5]. Bilateral orchiectomy is one classical strategy for androgen suppression; however, this method is associated with numerous side effects and risk factors [4] and results in castration-resistant prostate cancer (CRPC).…”
Section: Current Treatments For Prostate Cancermentioning
confidence: 99%
“…The possibility that doxorubicin might promote therapeutic responses in off-label clinical settings has recently been investigated in individuals with (1) hepatocellular carcinoma (HCC), as a standalone palliative regimen compared with 5-fluorouracil, folinic acid, and oxaliplatin; 63 (2) non-metastatic osteosarcoma, in combination with cisplatin high-dose ifosfamide (an alkylating mustard with a broad antineoplastic activity), cisplatin, and high-dose methotrexate; 64 (3) advanced prostate cancer, in the context of androgen deprivation therapy; 65 (4) tumors of the urothelial tract, either in its pegylated form as a single agent or combined with cisplatin, ifosfamide, and gemcitabine (a nucleoside analog licensed for the treatment of pancreatic cancer, NSCLC, breast carcinoma, and ovarian cancer); 66 , 67 as well as (5) in pediatric patients affected by relapsed or refractory extracranial non-hematopoietic solid tumors, in the context of oxaliplatin-based chemotherapy 68 . Conversely, epirubicin has been investigated as a potential alternative to standard therapeutic protocols in subjects bearing (1) advanced gastresophageal tumors, in combination with conventional cytotoxic agents and/or panitumumab, an FDA-approved monoclonal antibody specific for the epidermal growth factor receptor (EGFR); 69 , 70 or (2) transitional bladder carcinoma, as a second-line intervention for individuals who failed cisplatin- and gemcitabine-based first-line chemotherapy 71 .…”
Section: Update On Clinical Reportsmentioning
confidence: 99%
“…Results from recent and ongoing clinical trials showed the survival benefits for prostate cancer patients when docetaxel is introduced in the treatment regimen early in the stage of hormone sensitive disease [5, 6]. Due to severe side effects come with chemotherapy, poor general health condition is one of the absolute contraindications for patients ineligible for docetaxel treatment [7, 33, 34]. The PEG- b -PLA micelle system with minimal side effects and high capability of delivering poorly water-soluble drugs offers a chemotherapeutic delivery system that allows the inclusion of prostate cancer patients with frail condition.…”
Section: Resultsmentioning
confidence: 99%